PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN LITERASI SAINS SISWA SMP PADA PEMBELAJARAN IPA - Nurul Firdausi Nuzula; Elok Sudibyo (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
This study aimed to describe the improvement of students' scientific literacy by implementing the problem-based learning model. The method in this research is pre-experiment with one group pretest posttest design. The subject in this study were 20 students of the VIII I class in SMP Negeri 32 Surabaya. The implementation of the problem-based learning model is very good according to the syntax. The results N-Gain obtained through the pretest and posttest of scientific literacy in the medium category. The implementation of the problem-based learning model obtained positive responses from students with a very good category that supports the growth of students' scientific literacy skills. Based on the result, it can be concluded that the problem-based learning models implementation improved students’ scientific literacy in the additive. The aspect of competence/scientific process was the aspect that has the highest improvement in the medium category.